Question
Simplify completely: \( -9 \sqrt{27}-3 \sqrt{3} \) Answer \( =\square \)
Ask by Bowman Knight. in the United States
Feb 04,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( -30\sqrt{3} \)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Extra Insights
To simplify \( -9 \sqrt{27} - 3 \sqrt{3} \), we first simplify \( \sqrt{27} \): \[ \sqrt{27} = \sqrt{9 \times 3} = \sqrt{9} \cdot \sqrt{3} = 3\sqrt{3}. \] Now substituting back, we have: \[ -9 \sqrt{27} = -9 \times 3\sqrt{3} = -27\sqrt{3}. \] Now combine this with the second term: \[ -27\sqrt{3} - 3\sqrt{3} = -30\sqrt{3}. \] Thus, the simplified form is: \[ \boxed{-30\sqrt{3}}. \]